Harmful Algal Blooms (HABs): track them like a scientist. (3rd July 2019) - Curran, Mary Carla; Richlen, Mindy L.
Abstract: Marine phytoplankton comprise the foundation of oceanic food webs and generate most of the Earth's oxygen. Of the many phytoplankton species in the ocean, a few dozen produce potent toxins, and at high concentrations can form what are called Harmful Algal Blooms (HABs) or "red tides" that can discolor marine waters. Managers and scientists have been monitoring coastal waters and shellfish resources for HABs and their toxins to ensure seafood safety and understand why blooms occur. This educational activity focuses on a prominent HAB species that causes paralytic shellfish poisoning (PSP). Students will learn about the importance of HABs and PSP, as well as how scientists collect and use data to understand and predict blooms. Students will plot data on HAB species collected by scientists over multiple years of sampling. Students will also plot results over time and across regions, report on observed patterns, and complete grade-appropriate calculations. Lastly, group discussion will focus on determining whether geographic patterns exist that might influence where shellfish beds are closed. This activity is timely given the widespread wildlife mortalities and beach closures due to Florida red tide in 2017-2018, as well as widely publicized dog deaths in 2019 caused by exposure to freshwater cyanobacteria (blue-green algae) blooms.